Effects of inherent moisture contents on lignite conversion in the absence and presence of steam as reaction atmosphere - Bai, L.; Zhang, Shu; Zhang, K.; Wang, Y.; Xu, K. (2013)
This study is to investigate the influence of inherent moisture contents on Shengli lignite conversion using different particle sizes with and without steam as reaction atmosphere. A drop tube quartz reactor was used for conducting all the experiments. For the large coal particle sizes (0.9-2mm) in the inert gas atmosphere, the increase in moisture contents in coal did not always see the increase in coal conversion at 900 °C, for which the fast "escape" of moisture before inner area of coal particles reached the gasification temperature should be the main reason. For the small coal particle sizes (less than 0.075mm), the heat could immediately transfer into the inner particles and initiated the reaction between coal and the inherent steam, thus resulting in the increasing coal conversion and also more production of light gases. In the presence of steam for the reaction atmosphere, decreasing char yields with increasing inherent moisture content for large coal particle size was found as the transferring speed of inherent steam inside the coal particles was getting slow, compared to the case when the reaction atmosphere was ultra pure nitrogen. Furthermore, the reactivity of chars from pyrolysis was apparently different from that of chars from gasification, partially owing to the change in char structure caused by char-steam reactions.